Damage of central nervous system synapses at brain diseases: membrane mechanisms and methods of correction - Fedorovich, Sergei V.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2023)
Diseases of the central nervous system are a serious medical and social problem. Many of them are incurable or difficult to treat pharmacologically. Synapses damaging by different origin (synapthopathies) leading to malfunctioning synaptic transmission and pathological modification of nervous tissue often is underlied in brain diseases. Various objects are used to study the functional properties of synapses, one of the most popular being isolated neuronal presynaptic endings synaptosomes retaining intact plasma membrane and majority intracellular regulating and energetic system of neuron. This review analyses the results of our own research and the work of the world’s leading scientific centres, revealing important aspects of the pathogenesis of the brain, focused on data obtained using synaptosomes. The analysis showed that the pathogenesis of various brain diseases is based on both the accumulation of specific proteins and non-specific physicochemical factors. The most important examples of both types of influences are amyloid peptide synthesis, increase in the extracellular concentration of glutamate and pH decrease. These changes are characteristic of both ischemic stroke and many neurodegenerative diseases. It has been established that extracellular acidification leads to the formation of reactive oxygen species in the electron transport chain of synaptosomal mitochondria, and an increase in the concentration of glutamate in the incubation medium activates NADPH oxidase of the plasma membrane of synaptosomes followed by reactive oxygen species generation in extracellular space. Hypoglycemia, a serious complication of diabetes mellitus, leads to inhibition of exocytosis in synaptosomes, which may be a protective mechanism rather than a damaging effect. Several factors were identified that can be used for synaptic dysfunction correction in diseases of the central nervous system. So, epilepsy can be treated by the ketogenic diet, when carbohydrates are replaced by fats in the ration, which leads to the synthesis of ketone bodies, primarily β-hydroxybutyrate. It was shown using synaptosomes as an experimental model, that β-hydroxybutyrate inhibits endocytosis, which may be the reason for the anticonvulsant effect of the ketogenic diet. Another way to correct the work of synapses are nootropic drugs. It has been shown that glycine and piracetam, which have nootropic properties, are able to induce the activation of presynaptic inhibitory receptors, followed by the efflux of chlorine ions from the cytosol and depolarisation of the plasma membrane. The lowering of the depolarisation threshold for the neurotransmitter release can explain the nootropic effect of these compounds. So, the functioning of the presynaptic terminal of a neuron can be impaired or vice versa corrected by specific targets manipulation. Activation or deactivation of identified targets can be the basis for various brain diseases therapy.